Sick Building Syndrome and the Problem of Uncertainty : Environmental Politics, Technoscience, and Women Workers - Murphy, Michelle (Claudette Michelle) (Book collections on Project MUSE., 2006)
An account of sick building syndrome and the large number of historical conditions--office worker protests, feminism, ventilation engineering, toxicology, etc.--that coalesced to give this phenomenon real existence.